Principal's Leadership Style In Improving Teacher Performance At SMK Negeri 1 Kutalimbaru - Miftah Royyani; Muhammad Rifa'i; Nurika Khalila Daulay (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
This research was conducted so that principals are able to make a habit of providing guidance to teachers related to all the problems faced so that teachers are able to maximally and professionally carry out their performance professionally, in the sense of being good but must be firm in carrying out their duties as principals. This research is a qualitative research method with a descriptive study This research includes field research with a phenomenological approach. In this case, the data collection techniques used are interviews, observations and documentation studies. The data analysis techniques used in this research are 1) Data Reduction 2) Presentation of Data (Data Display); 3) Conclusion Drawing. The results showed that the performance of teachers at SMK Negeri 1 Kutalimbaru included: 1). Teacher performance in planning the learning process. 2). Teacher performance in learning implementation. 3). Teacher performance in learning evaluation. 4). Efforts to improve teacher performance made by principals are by conducting training, workshops and also motivational seminars. The leadership styles applied by the principal of SMK Negeri 1 Kutalimbaru are: 1). Democratic leadership type. 2). Visionary leadership type. 3). Transformational leadership type. The driving factors of the principal's leadership in improving the performance of teachers at SMK Negeri 1 Kutalimbaru include: 1).The principal's ability to manage planning. 2).Synergistic relationship among school members. The factors that hinder the principal's leadership in improving teacher performance include: 1). Inadequate facilities and infrastructure. 2). The low ability of teachers to utilize technology. 3). Lack of support from parents